UCAnDoModels: A Context-based Model Editor for Editing and Debugging UML Class and State-Machine Diagrams - Pourali, Parsa; Atlee, Joanne M. (ACM/IEEE, 2019)
Practitioners face cognitive challenges when using model editors to edit and debug UML models, which make them reluctant to adopt modelling. To assist practitioners in their modelling tasks, we have developed effective and easy-to-use tooling techniques and interfaces that address some of these challenges. The principle philosophy behind our tool is to employ cognitive-based techniques such as Focus+Context interfaces and increased automation of modelling tasks, in order to provide the users with valid, relevant and meaningful contextual information that are essential to fulfil a focus task (e.g., writing a transition expression). This paper presents our approach, which we call User-Centric and Artefact-Centric Development of Models (UCAnDoModels), and discusses two usecase scenarios to demonstrate how our tooling techniques can enhance the user experience with modelling tools.
© ACM 2019 Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page. Copyrights for components of this work owned by others than ACM must be honored. Abstracting with credit is permitted. To copy otherwise, or republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee. Request permissions from permissions@acm.org.